Exploring Situational Triggers of Intimate Partner Femicide within the Ecological Framework: Evidence from Married Females in China - Zhang, Bo (Victims & offenders, 2025)
In the extensive research on intimate partner violence (IPV), the emphasis on female victimization has led to a detailed exploration of intimate partner femicide (IPF) as its most severe outcome. Although numerous studies have investigated IPF risk factors, the specific situational triggers leading to these incidents remain under-examined, particularly in the Chinese context, where research on this topic is notably limited. This study addresses this gap by analyzing 238 Chinese judicial cases of IPF involving married females. Utilizing an ecological framework and qualitative analysis, the study identifies situational triggers of IPF across various levels: societal (e.g. bride price conflicts, return to Niangjia, oppression and termination of economic dependence in uxorilocal marriage), relationship (e.g. broken intimate relationships, infidelity, and situational arguments in marital life), and individual (e.g. offender with mental illness, offender suicide, and alcohol use by the offender). The study, however, finds no evidence that community-level factors serve as situational triggers of IPF. This study not only empirically validates the identified situational triggers of IPF but also enhances the ecological framework’s applicability in understanding this phenomenon.